2021
DOI: 10.3389/fphys.2021.708061
|View full text |Cite
|
Sign up to set email alerts
|

Is Oxidative Stress the Link Between Cerebral Small Vessel Disease, Sleep Disruption, and Oligodendrocyte Dysfunction in the Onset of Alzheimer’s Disease?

Abstract: Oxidative stress is an early occurrence in the development of Alzheimer’s disease (AD) and one of its proposed etiologic hypotheses. There is sufficient experimental evidence supporting the theory that impaired antioxidant enzymatic activity and increased formation of reactive oxygen species (ROS) take place in this disease. However, the antioxidant treatments fail to stop its advancement. Its multifactorial condition and the diverse toxicological cascades that can be initiated by ROS could possibly explain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 142 publications
0
9
0
Order By: Relevance
“…Thus, increased levels of reactive oxygen species lead to alterations in blood flow resistance and endothelial regulatory response is impaired by the disruption of endothelium-dependent nitric oxide signaling [ 66 68 ], resulting in increased microvessel permeability and impaired microvascular endothelial function [ 67 , 69 71 ]. Hydrogen peroxide, superoxide derivates, hydroxyl radical or peroxynitrites increase endothelial calcium concentration in time- and dose-dependent manner causing dysregulation in calcium homeostasis, acting as proapoptotic factor in cerebral vascular cells [ 66 , 70 , 72 ]. In addition, oxidative stress has a key role in insulin resistance and progression of diabetes [ 73 , 74 ] and diabetic mice show vascular alterations associated with increased oxidative stress, pericyte dysfunction and cerebrovascular integrity compromise [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increased levels of reactive oxygen species lead to alterations in blood flow resistance and endothelial regulatory response is impaired by the disruption of endothelium-dependent nitric oxide signaling [ 66 68 ], resulting in increased microvessel permeability and impaired microvascular endothelial function [ 67 , 69 71 ]. Hydrogen peroxide, superoxide derivates, hydroxyl radical or peroxynitrites increase endothelial calcium concentration in time- and dose-dependent manner causing dysregulation in calcium homeostasis, acting as proapoptotic factor in cerebral vascular cells [ 66 , 70 , 72 ]. In addition, oxidative stress has a key role in insulin resistance and progression of diabetes [ 73 , 74 ] and diabetic mice show vascular alterations associated with increased oxidative stress, pericyte dysfunction and cerebrovascular integrity compromise [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The brain, generally presenting very low antioxidant levels, is particularly susceptible to oxidative damage [ 114 ]. In AD, brain regions such as the prefrontal cortex, hippocampus, and amygdala are more vulnerable to oxidative damage, dendritic shrinking, and amygdala hyperactivity specifically triggered by oxidative stress [ 115 ]. In the present study, on the amygdala level, it was observed that single-dose administration of Aβ1-42 efficiently induced oxidative state-like changes, such as elevated protein oxidation ( p = 0.0084) ( Figure 6 E) and lipid peroxidation ( p = 0.0084) ( Figure 6 F) rates, as well as a reduced level of GSH ( p = 0.0103) ( Figure 6 D) and decreased activity of antioxidant enzymes CAT ( p = 0.0027) ( Figure 6 A), SOD ( p = 0.0066) ( Figure 6 B), and GPX ( p = 0.0027) ( Figure 6 C).…”
Section: Resultsmentioning
confidence: 99%
“…High levels of oxidative stress may induce OPC death, but sublethal levels can disrupt OPC differentiation (Lloret et al, 2021; Miyamoto et al, 2013; Spaas et al, 2021). In‐vitro, ROS exposure altered the expression of oligodendrocyte differentiation regulators, increasing the expression of inhibitors and reducing the expression of positive regulators (French et al, 2009; Lim et al, 2016; Spaas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%